Acute intestinal obstruction secondary to left paraduodenal hernia: a case report and literature review - Al-Khyatt, Waleed; Aggarwal, Smeer; Birchall, James; Rowlands, Timothy E. (BioMed Central, 2013)
Introduction: An internal hernia is a protrusion of bowel through a normal or abnormal orifice in the peritoneum or mesentery. Although they are considered as a rare cause of intestinal obstruction, paraduodenal hernias are the most common type of congenital hernias. Methods: A literature search using PubMed was performed to identify all published cases of left paraduodenal hernia (LPDH). Results: In Literature search between 1980 and 2012 using PubMed revealed only 44 case reports before the present one. Median age was 47 years (range 18 – 82 years). Nearly 50% reported previous mild symptoms. Two-third of patients required emergency surgery in form of laparotomy or laparoscopic repair. Reduction of hernia contents with widening or suture repair of the hernia orifice were the most common standards in surgical management of LPDH. Conclusion: Intestinal obstruction secondary to internal hernias is a rare presentation. High index of suspicion and preoperative imaging are essential to make an early diagnosis in order to improve outcome.